Analysis The Role Of Infrastructure In Effective Learning - Deassy Yunita; Balqis Fadiah; Lainatusshifa Lainatusshifa; Putri Maulida (Pusat Riset dan Inovasi Nasional, 2024)
This research explores the crucial role of infrastructure in effective learning, focusing on the impact of facilities and environmental conditions in educational settings. It emphasizes the need for adequate infrastructure to support teaching and learning processes. The study reviews relevant literature, indicating a positive relationship between school facilities and student performance. Employing a qualitative research method, the researcher uses a library research design to gather and analyze data. The discussion highlights the importance of infrastructure in creating conducive learning environments, emphasizing factors such as classroom design, technology integration, and overall school conditions. The findings emphasize that a well-designed and well-equipped school infrastructure contributes significantly to student achievement and overall educational quality. The study concludes with a call to prioritize infrastructure development to enhance the learning experience and improve educational outcomes.